2022
DOI: 10.33369/jk.v6i2.21658
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perceptions Toward Practical Online Learning in Physical Education: A Case Study

Abstract: This research aims to evaluate the e-learning system in practical courses in the Physical Education Department based on psychomotor learning outcomes. The research method used is descriptive qualitative, using a survey design with a cross-sectional type for program evaluation. In this case, the program analyzed for evaluation is online-based learning in practical courses based on psychomotor learning outcomes during the Covid 19 pandemic. Questionnaires, interviews, observations, and documentation were used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…This research study gained information on student experiences by ascertaining their opinions of the distance education process during the COVID-19 pandemic. Similar studies are also found in the literature (Arslan, 2021;Çiçek et al, 2020;Genç et al, 2020;Ghoreyshi, 2022;Günal, 2022;Er-Türküresin, 2020;Hidayat et al, 2022;Kaysi, 2020;Nikolopoulou, 2022;Özer, 2022;Tuzcuoğlu, 2022). Arslan (2021), Genç et al (2020), Ghoreyshi (2022), Günal (2022), Er-Türküresin (2020), Hidayat et al (2022), Nikolopoulou (2022), and Tuzcuoğlu (2022) examined the experiences of students about the distance education process during the COVID-19 pandemic.…”
Section: Conclusion and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This research study gained information on student experiences by ascertaining their opinions of the distance education process during the COVID-19 pandemic. Similar studies are also found in the literature (Arslan, 2021;Çiçek et al, 2020;Genç et al, 2020;Ghoreyshi, 2022;Günal, 2022;Er-Türküresin, 2020;Hidayat et al, 2022;Kaysi, 2020;Nikolopoulou, 2022;Özer, 2022;Tuzcuoğlu, 2022). Arslan (2021), Genç et al (2020), Ghoreyshi (2022), Günal (2022), Er-Türküresin (2020), Hidayat et al (2022), Nikolopoulou (2022), and Tuzcuoğlu (2022) examined the experiences of students about the distance education process during the COVID-19 pandemic.…”
Section: Conclusion and Discussionsupporting
confidence: 79%
“…Similar studies are also found in the literature (Arslan, 2021;Çiçek et al, 2020;Genç et al, 2020;Ghoreyshi, 2022;Günal, 2022;Er-Türküresin, 2020;Hidayat et al, 2022;Kaysi, 2020;Nikolopoulou, 2022;Özer, 2022;Tuzcuoğlu, 2022). Arslan (2021), Genç et al (2020), Ghoreyshi (2022), Günal (2022), Er-Türküresin (2020), Hidayat et al (2022), Nikolopoulou (2022), and Tuzcuoğlu (2022) examined the experiences of students about the distance education process during the COVID-19 pandemic. Tuzcuoğlu (2022) examined the opinions of academicians about the distance education process.…”
Section: Conclusion and Discussionsupporting
confidence: 79%
“…Gestures that need to be considered are hand Moreover, after the pandemic, there was a marked difference in motivation (Campillo-Ferrer & Miralles-Martínez, 2021) to study, which had been hampered by the pandemic and then gradually returned to normal. However, the enthusiasm to return to learning is also affected, and a wrong understanding is produced due to the usage of telecommunication media, making it easy make children lazy to do learning seriously (Hidayat, Rohyana, & Lengkana, 2022). this also causes some delays in learning, which does not mean that online learning is only focused on providing the material as a whole on the internet.…”
Section: Discussionmentioning
confidence: 99%